Prevalence of hepatitis B and C virus infections among visceral leishmaniasis patients: a systematic review and meta-analysis - Assefa, Muluneh; Biset, Sirak (Frontiers in Microbiology, 2024)
Background: Visceral leishmaniasis (VL) patients are at high risk of acquiring hepatitis B virus (HBV) and hepatitis C virus (HCV) infections during multiple injections and the antileishmanial treatment possesses a potential hepatotoxic effect. This systematic review and meta-analysis determined the pooled prevalence of HBV and HCV infections in VL patients.This study was registered in the International Prospective Register of Systematic Reviews (PROSPERO), with the assigned number CRD42024516889, and conducted as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A literature search was performed using PubMed, Medline, EMBASE, Google Scholar, Web of Science, and Science Direct databases. Data were extracted using Microsoft Excel and analyzed using STATA version 11.0 software. A random-effects model was used to estimate the pooled effect size of outcome variables across studies with a 95% confidence interval and was displayed in a forest plot. The I 2 statistic was used to check for heterogeneity. The presence of publication bias was determined using a funnel plot and Egger's test with a p-value < 0.05 evidence of statistically significant bias.Results: Among 216 retrieved records, 7 studies were eligible for systematic review and meta-analysis. A total of 937 VL patients were examined, revealing that 105 and 93 were infected with HBV and HCV, respectively. The pooled prevalence of HBV was 16.15% (95% CI: -4.10-36.39), with a significant heterogeneity (I 2 = 91.4%, p < 0.001). The combined prevalence of HCV was 13.74% (95% CI: 1.32-26.16, I 2 = 71.6%, p = 0.003). The funnel plot (symmetry), and Egger's test in both HBV (p-value = 0.650) and HCV (p-value = 0.841) revealed no publication bias. In subgroup analysis, high HBV and HCV prevalence was detected in Sudan; 20.64% (95% CI: -13.60-54.88) and India; 18.26% (95% CI: -0.40-36.92%), respectively.This study revealed a high prevalence of both HBV and HCV infections in VL patients. In subgroup analysis, the prevalence of HBV and HCV was high in Sudan and India, respectively. Therefore, screening of VL patients for HBV and HCV, vaccination of VL patients in endemic regions, and collaboration between kala-azar and hepatitis elimination programs are required.